Using Public Expenditure Tracking Surveys to Monitor Projects and Small-Scale Programs : A Guidebook - Koziol, Margaret; Tolmie, Courtney (World Bank, 2012)
The goal of this guidebook is to serve as a starting point for civil society organizations, as well as Bank teams interested in conducting Public Expenditure Tracking Surveys, both on a small and larger scale. It is designed to lead a research team from idea inception to results dissemination, while emphasizing the importance of utilizing evidence to influence policy, regardless of whether it is on a macro or micro-level. Though the World Bank has been at the forefront of efforts to measure the effectiveness of service delivery, it is hoped that Bank teams and civil society alike will take the research one step further and empower citizen users to keep service providers accountable through information dissemination and citizen engagement efforts.